Induced polygenic variations through γ-rays irradiation and selection of novel genotype in chamomile (Chamomilla recutita [L.] Rauschert). (2nd September 2019) - Lal, Raj Kishori; Chanotiya, Chandan Singh; Singh, Ved Ram; Dhawan, Sunita Singh; Gupta, Pankhuri; Shukla, Shama; Mishra, Anand
Abstract: Purpose: To develop elite mutants in chamomile ( Chamomilla recutita [L.] Rauschert) for increasing the quantity and quality of essential oil rich in acetylenic compound (2 Z, 8 Z )-matricaria acid methyl ester by applying γ -rays irradiation. Molecular and chemical analysis was performed for ithe dentification/differentiation of mutant genotype. Materials and methods: Chamomile ( Chamomilla recutita [L.] Rauschert) variety Vallary seeds were irradiated by applying γ -rays irradiation at 100, 200, 300, 400, 500, 600, 700, 800, 900 and1000 Gy doses at a dose rate of 55 Gy/min and mutants were isolated and analyzed for the quantity and quality of essential oil. The oil was found to be rich in acetylenic compound (2 Z, 8Z)-matricaria acid methyl ester and the results obtained were validated using gas chromatography (GC) coupled with either Flame Ionization detection (GC-FID) or mass spectrometer (GC-MS), and nuclear magnetic resonance (NMR). Results: The selected mutant SELM-1 (Selection Mutant-1) showed the production potential of 7.00–7.50 q ha −1 dry flowers and 6.00–6.50 kg ha −1 essential oil yield. Essential oil of mutant SELM-1 contained in [(2 Z, 8 Z )-matricaria acid methyl ester] (76–80%) useful in cosmetic, perfumery, and pharmaceutical industries. Conclusion: γ -rays irradiation method is a very efficient mutation breeding method for chamomile crop. GC-FID or GC-MS and NMR methods are found to be the most powerful methods for screening of essential oil chemical compounds isolated from the mutants. The novel mutant (SELM-1) is very promising in terms of high flower and essential oil yield rich in acetylenic compound (2 Z, 8 Z )-matricaria acid methyl ester (76–80%), hence, it was released as variety in Council of Scientific & Industrial Research (CSIR)-Central Institute of Medicinal and Aromatic Plant (CIMAP), Lucknow U.P. (India) named as CIM-Ujjwala for commercial cultivation.